Sistem Informasi Manajemen Data Penduduk Berbasis Website - M. Sarusu, Armansyah; Akmila, Dyna; Wijana, Miki; Habiby, Mohammad Erdda (INTERNAL (Information System Journal), 2023)
Management is the process of planning, coordinating, directing, and controlling resources to a set goal. Population data is an important asset in planning and decision-making. Website-based information systems can increase government transparency and involve the public in the management of population data, facilitating computerized data processing so that it becomes more efficient and efficient. Research methods use qualitative methods to understand and explain phenomena in a good context. Data collection techniques include interviews, observations, documentation, library studies, and implementation. Use case and class diagrams are used to identify and describe functions or interactions between actors and systems. In running the system use three actors namely IT staff, admin and head of the hamlet. The purpose of the website is that users can obtain relevant information, make transactions, communicate, interact with administrators and other users globally and in real time. The results showed that with the creation of an information system of population deposition management in Nagreg villages can improve the efficiency in the deposition process and reduce human error, easier to obtain and update information on population data.